The Independent Learning (Nature-Based Learning): Outdoor Study Arabic Learning Nature School Jambi City - Muhammad Sobri; Eva Iryani; Mulyadi (Universitas Yudharta Pasuruan, 2021)
This study describes nature-based learning as an offer of new learning outside the classroom for Arabic learning at the Jambi City Natural School to implement independent learning in Indonesia. Field research used a qualitative approach rooted in natural settings as data integrity. Well, interviews, observations, and documentation as a comprehensive data collection technique. The findings of the research, which located at the al-Fath natural school in Jambi, show that nature-based fig language learning is carried out by (1) an integrative curriculum of three curricula: Nature, Integrated Islam, and the National Education by applying the spirit of independent learning and make nature. 2) outdoor class based on contextual approach with the application of the saung mode backpacker and live-in. Program career days and Quran week used active learning methods Implemented in Arabic learning. 3). Supporting factors: open learning places and teachers applying various variations of teaching methods. Furthermore, the inhibiting factors: the use of big themes, combining Arabic language material with other materials, teacher competence, and parental cooperation. Arabic based on an integrative curriculum is a new paradigm in outdoor class-based Arabic learning, which is currently primarily taught in class as a unit of mainstream language learning theory.